2012
DOI: 10.1016/s2255-4971(15)30132-4
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying Tendinopathy: A Local or a Systemic Condition?

Abstract: Objective: To evaluate the relationship between cases of calcifying tendinopathy of the shoulder and symptomatic metabolic diseases such as kidney stones, gallstones and gout. Methods: Calcifying tendinopathy of the shoulder was diagnosed in 63 patients between May 2007 and September 2011. All the patients were treated by the same orthopedic surgeon and were interviewed to gather the following data: age at diagnosis, sex, affected side, dominant side, body mass index (BMI), smoking status and previous historie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(13 reference statements)
1
3
0
1
Order By: Relevance
“…Our study confirmed, similarly to previous findings, [ 7 ] that nephrolithiasis is significantly more common in patients with calcific RCT. However, to the best of our knowledge, this is the first study to reveal a significant positive association between calcific RCT and cholelithiasis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study confirmed, similarly to previous findings, [ 7 ] that nephrolithiasis is significantly more common in patients with calcific RCT. However, to the best of our knowledge, this is the first study to reveal a significant positive association between calcific RCT and cholelithiasis.…”
Section: Discussionsupporting
confidence: 93%
“…[ 6 ] Unique is the study, carried out by Ejnisman, suggesting an association with nephrolithiasis, the latter being present in 32% of patients suffering from calcific RCT. [ 7 ] However, no association with cholelithiasis has been demonstrated to date.…”
Section: Introductionmentioning
confidence: 99%
“…В этом случае могут развиться следующие осложнения: адгезивный капсулит, разрыв ротаторной манжеты, остеолиз большого бугорка плечевой кости, оссифицирующий тендинит [29]. Также есть сообщение об ассоциации кальцифицирующего тендинита с почечнокаменной болезнью у 33% лиц из 63 пациентов по сравнению с 9% в контрольной группе [30].…”
Section: эпидемиологияunclassified
“…Benno et al in study of 63 patients described association of calcifying tendinitis with renal lithiasis in 33% of individuals in comparison with 9% in control group. 23 Pain being the major clinical symptom Neer described different causes of pain occurring Calcifying tendinitis 24 (Table 1).…”
Section: Clinical Featuresmentioning
confidence: 99%